La digrafía y su incidencia en el proceso de enseñanza aprendizaje de los estudiantes del quinto y sexto grado sección matutina de Educación Básica de la Escuela Federación Deportiva de Cotopaxi de la provincia de Cotopaxi, año lectivo 2 016 -2 017. - Barreno Flores, Cristian Stalin (2018)
The research contains fundamental aspects to understand this problem since the country educational institutions have different learning problems which are mostly in children. One of them is the dysgraphia which is causing a big impact in writing learning, such as confusion and skipping letters, words or syllables, perceptive difficulties, motor and side effects causing tension in students. The root of the problem about dysgraphia can be said that was born by professors’ lack of interest or concern because they do unplanned activities in the classroom, so it caused dangerous problems about writing learning in children, this is blocking the children’s cognitive and motor development. Another fact of the problem is the lack of knowledge about new methods and techniques, which would help to develop abilities and skills. This research is important because it will help to improve significantly the writing learning process. The development of this research was conducted inside of the mentioned school and using bibliographical tools since the whole theory needs standards from different authors, the approach of this research was to develop conferences and workshops about the effect of dysgraphia in the teaching learning process of students of fifth and sixth grade from the “Federación Deportiva de Cotopaxi” school. Improving the teacher’s knowledge about the topic, generating awareness about the culture development, helping the integral growth, and academic development necessities. The characteristic of this research is to be based in books and in the field, conducted inside of the elementary school, based in a lot of bibliographical content because its contextualization and theoretical contributions need ideas and standards from diverse authors; in this research all the methodological strategies were considered in all the instances; in the final phase a proposal was elaborated about guiding workshops with easy comprehension and application instruments. The research results show that 75% of students have writing difficulties, this is alarming because it becomes a difficult problem to solve. This research gives a tool, so teachers can support and find the cause of the problem as well as detect it on time.